The connecting leader : serving concurrently as a leader and a follower - Jaser, Zahira (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Previous books of the Leadership Horizon Series showed unequivocally how both leaders and followers play an equally important part in the co-production of leadership outcomes, and how leader and follower identities are fluid, so that the same individual can enact both at different times. This book stretches the notion of leadership a step further by exploring the co-enactment of both roles, identities, and positions of leader and follower by one same individual. This individual is defined as a connecting leader, as in this co-enactment he/she functions as connector between different leadership relationships. The concept of connecting leader emerges from the observation that most individuals in organizations engage in the leader-follower role co-enactment: managers, pulled between executives and reportees; CEOs, between the board and the head of departments; or employees involved in cross functional teams, leading and following in different degrees, subject to their expertise. Yet, despite its pervasiveness this concept is at best under theorized by the literature, which, dominated by dyadic and romanticized views, mostly presents the roles as enacted by separate individuals facing each other. To advance our understanding of connecting leaders the editor proposes to shift our focus on leadership in three ways: to unpack the interconnectedness and interplay of leader and follower identities; to investigate the tensions arising from the co-enactment and how these can be overcome; to widen the way in which we study leadership, through new configurations (e.g. leadership triads) and ontologies; and finally to consider the similarities between leading and following. The book chapters are organized to mirror these areas of exploration. Understanding leadership from a perspective that acknowledges that many individuals in organizations are not just leaders or followers, but both, democratizes the way we theorize leadership, and moves us further away from the temptation to romanticize it"-- Provided by publisher.
Includes index.
Keywords: Leadership.; Followership.; Business & Economics -- Leadership.; Management: leadership and motivation.; elektronické knihy; electronic books